Exploring balanced modal split for freight transportation system: A case of the central region of South Africa - Dillip Kumar Das; Boiki J Mokobori; Rakesh Gopinath (Transportation Research Interdisciplinary Perspectives)
Ensuring sustainability in transportation systems demands a harmonious distribution of freight. In the regional context of South Africa, road and rail transportation play pivotal roles, yet a significant imbalance exists, posing sustainability challenges. This study aims to identify key factors influencing freight transport, develop empirical cost models, and simulate scenarios to achieve equilibrium in regional freight distribution. Employing survey research, data was collected from freight companies and analysed using inferential statistics and empirical modelling. It employed a utility choice function model for simulating scenarios conducive to achieving a balanced freight transport system. Findings suggest that currently, compared to rail freight, road freight transport dominates, leading to an imbalanced system. Critical factors that influence include load cost, loading/offloading times, fuel expenses, and travel duration. However, sensitivity analyses revealed that targeted reductions in travel time, loading/offloading times, load cost, and fuel expenses could lead to a substantial shift towards rail transport, promoting a more balanced system. This study provides actionable insights for stakeholders. By addressing influential variables, such as load cost, loading/offloading times, fuel expenses, and travel duration, the freight industry can work towards equitable coexistence of road and rail transport. This study highlights the prevalence of road-based freight transport in the region and demonstrates the potential for equilibrium through interventions in key variables.